Routinization and employment: Evidence for Latin America - Leonardo Gasparini; Carlo Lombardo; Irene Brambilla; Andrés César; Guillermo Falcone (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
We study changes in employment by occupations characterized by different degree of exposure to routinization in the six largest Latin American economies over the last two decades. We combine our own indicators of routine task content based on information from the Programme for the International Assessment of Adult Competencies (PIACC) with labor market microdata from harmonized national household surveys. We find that the increase in jobs was decreasing in the automatability of the tasks typically performed in each occupation, and increasing in the initial wage, a pattern more consistent with the traditional skill-biased technological change than with the polarization hypothesis.
Keywords: J21; J23; J24; O33; 330; jobs; employment; technology; automation; routinization; Latin America